USING MIND MAPPING TECHNIQUE TO IMPROVE STUDENT'S ABILITY IN READING DESCRIPTIVE TEXT - Widiyasari, - (2010)
ABSTRACT The research entitled Using Mind Mapping Technique to Improve Students' Ability in Reading Descriptive Text: A Quasi Experimental Study of Seventh Grade Students at SMPN 12 Bandung. The research investigated the effectiveness of mind mapping technique in teaching reading descriptive text to the seventh graders of SMPN 12 Bandung. Quasi experimental with pre and post test nonequivalent group design was used in the research. Sample of the research was 70 students divided into experimental and control group; each group consists of 35 people. Reading test was used as the research instrument. The data were then analyzed by using t-test computation to examine whether or not the independent variable gave significant effect to the dependent variable. Moreover, to answer the second and the third research questions, interview was used in the research. From the scores of independent t-test, experimental group students have higher reading scores (M = 81.4 SE = 9.33) than the control group students (M = 76.1, SE = 8.49), t (68) = 2.502, p < .05, with the large effect size r = 0.705). Results showed that mind mapping technique gave significant result in teaching descriptive text. In addition, the students' responses from the interview also proved that mind mapping technique has given some advantages in learning descriptive text. It can be concluded that several treatments of mind mapping technique was effective in improving students' ability in reading the descriptive text. The results of the research are expected to give some contributions in teaching learning process particularly in teaching reading skill for young language learners. Moreover, it would be better if the technique can be implemented to teach another skill such as speaking or writing.